2020
DOI: 10.1002/elps.202000100
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast gene markers detect diatom DNA in a drowned mice establishing drowning as a cause of death

Abstract: Diatoms are unicellular microalgae with cell wall made up of rigid silica found in all open water bodies. They thus resist degradation and hence are important tool to diagnose cause of death in drowned bodies. The nitric acid digestion method practiced conventionally in forensic science laboratories has limitations due to manual error. Plant chloroplast genes found in diatoms such as ribulose‐1,5‐bisphosphate carboxylase oxygenase (rbcL‐3P) and rbcL, universal plastidic amplicon (UPA), and photosynthesis I P70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The molecular study also revealed diversity in PCR amplicons for 13 fresh water diatoms (Table 1) using about 22 pairs of gene based PCR markers (Table ; Vinayak, 2020) run against standard DNA ladder of 100 kb size. It was observed that primers specific for gene locus DRR3 ‐1‐6, ScfcpA , Lhcf11 , SIT1 , LOC101218388 , SIT3 , SIT4 ‐1‐4, COI ‐ 5P 1‐6, and 18S rRNA 3‐4 did not amplify the diatoms at same PCR conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular study also revealed diversity in PCR amplicons for 13 fresh water diatoms (Table 1) using about 22 pairs of gene based PCR markers (Table ; Vinayak, 2020) run against standard DNA ladder of 100 kb size. It was observed that primers specific for gene locus DRR3 ‐1‐6, ScfcpA , Lhcf11 , SIT1 , LOC101218388 , SIT3 , SIT4 ‐1‐4, COI ‐ 5P 1‐6, and 18S rRNA 3‐4 did not amplify the diatoms at same PCR conditions.…”
Section: Resultsmentioning
confidence: 99%
“…This demonstrates that sequencing lineage trees not only identifies the diatom correctly but also gives information about its ancestorial origin from fresh water or marine water. This has wide application in phylogenetic studies, screening diatoms for biofuel (Khan et al, 2020; Khan et al, 2021; Kumar et al, 2018b; Kumar et al, 2018a; Vinayak et al, 2014; Vinayak et al, 2015), and use of diatoms in forensic science (Vinayak, 2020; Vinayak & Gautam, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation